Design and application of chitosan microspheres as oral and nasal vaccine carriers: an updated review - Islam, Mohammad Ariful (Dove Medical Press, 2012)
Chitosan, a natural biodegradable polymer, is of great interest in biomedical research due to its excellent properties including bioavailability, nontoxicity, high charge density, and mucoadhesivity, which creates immense potential for various pharmaceutical applications. It has gelling properties when it interacts with counterions such as sulfates or polyphosphates and when it crosslinks with glutaraldehyde. This characteristic facilitates its usefulness in the coating or entrapment of biochemicals, drugs, antigenic molecules as a vaccine candidate, and microorganisms. Therefore, chitosan together with the advance of nanotechnology can be effectively applied as a carrier system for vaccine delivery. In fact, chitosan microspheres have been studied as a promising carrier system for mucosal vaccination, especially via the oral and nasal route to induce enhanced immune responses. Moreover, the thiolated form of chitosan is of considerable interest due to its improved mucoadhesivity, permeability, stability, and controlled/extended release profile. This review describes the various methods used to design and synthesize chitosan microspheres and recent updates on their potential applications for oral and nasal delivery of vaccines. The potential use of thiolated chitosan microspheres as next-generation mucosal vaccine carriers is also discussed.